Sting [large type] - Brown, Sandra, 1948- (Grand Central Pub, 2016)
When Jordie Bennet and Shaw Kinnard lock eyes across a disreputable backwater bar, something definitely sparks. Shaw gives off a dangerous vibe that makes men wary and inspires women to sit up and take notice. None feel that undercurrent more strongly than savvy businesswoman Jordie, who doesn't belong in a seedy dive on the banks of a bayou. But here she is ... and Shaw Kinnard is here to kill her. As Shaw and his partner take aim, Jordie is certain her time has come. But Shaw has other plans and abducts Jordie, hoping to get his hands on the $30 million her brother has stolen and, presumably, hidden. However, Shaw is not the only one looking for the fortune. Her brother's ruthless boss and the FBI are after it as well. Now on the run from the feds and a notorious criminal, Jordie and Shaw must rely on their wits-and each other-to stay alive.